Domestication studies of wild agaric Macrocybe gigantea: Physical parameters - Brar, Gagan; Kaur, Munruchi; Kaur, Sukhdeep (Mushroom Research, 2023)
A wild edible mushroom, characterised by robust fruiting bodies growing in large caespitose clusters under Tectona grandis was collected from a local park in Patiala. This collection was identified as Macrocybe gigantea, based on morpho-anatomical characterization and through ITS1 and ITS4 and LSU primers. Chang and Miles (2004) have listed this species as a potentially edible mushroom. Taking this into account, along with fleshy robust fruiting bodies and the tropical growing habit, it was taken up for domestication. For any such studies, primarily the physical parameters need to be evaluated which would be the base for further domestication studies. The present paper deals the physical parameters best suited for the vegetative growth of this wild agaric.